Often Encountered but Rarely Reported: Challenges in Selecting Language(s) for Intervention in Bi/Multilingual Children with Autism Spectrum Disorder - Srikar, Malavi; Raju, Reny; Dadlani, Nikita; Swaminathan, Divya; Vaidhyanathan, Prathiksha; Meera, Shoba S. (Journal of Child Science, 2022)
India is a socioculturally and linguistically diverse country. Most often individuals grow up exposed to more than one language. Apart from exposure to native and community languages, there is a growing preference for English as the language of formal education and employment. Previous studies demonstrated that bilingual children with autism spectrum disorder (ASD) develop language similar to their monolingual nonverbal IQ-matched ASD peers. However, most of these studies have been conducted in countries in which English is the primary language for majority of the population. Although existing studies support a bilingual environment for children with ASD, professionals still seem to advise families' use of a monolingual approach. This paper reviews and discusses factors that influence the selection of language(s) for intervention in young children with ASD in bi/multilingual environments. These are discussed under three areas namely, (1) language environment of the child, (2) parent/caregivers' perspectives regarding bi/multilingual exposure, and (3) medium of education and availability of intervention services. This paper also highlights the complexities involved in the language selection process for intervention using four case vignettes. Based on the review and findings from the case vignettes, it is evident that there is a need for (1) sensitizing fellow professionals regarding the increasing shift toward a bi/multilingual approach, (2) formulating guidelines for this decision-making process, and (3) continuing to develop an evidence base for adopting multilingual approach for intervention in a socioculturally and linguistically diverse country like India.
Keywords: bilingual; multilingual; autism spectrum disorder; intervention; speech-language pathology